Hubungan Persepsi Kompetensi Pedagogik Guru Dengan Hasil Belajar Siswa Pada Mata Pelajaran Akhlak Di KMI Al-Ishlah Bondowoso - Kusuma, Hera; Jannah, Miftahul; Khoiriyah, Aimatul; Miasari; Prasetiya, Benny (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study aims to analyse the relationship between students’ perceptions of teachers’ pedagogical competence and students’ learning outcomes in the subject of Akhlak at KMI PI of Al Ishlah Islamic Boarding School, Bondowoso. The research employed a quantitative approach with an associative correlational design. The sample consisted of 60 students selected through purposive sampling. Data on perceptions of pedagogical competence were collected using a Likert-scale questionnaire, while data on learning outcomes were obtained from documentation of Akhlak subject scores. Relationship analysis was conducted using Spearman Rank correlation (SPSS 25), while simple linear regression was used as a supplementary analysis to identify the trend of the relationship. The results showed a Spearman correlation coefficient of 0.728 with a significance level of p < 0.001, indicating a positive, strong, and significant relationship between students’ perceptions of teachers’ pedagogical competence and Akhlak learning outcomes. Regression analysis revealed an R Square value of 0.522, indicating that 52.2% of the variance in learning outcomes can be explained by students’ perceptions of teachers’ pedagogical competence. In conclusion, the better students’ perceptions of teachers’ pedagogical competence, the higher the Akhlak learning outcomes achieved. Therefore, strengthening teachers’ pedagogical competence should be a key focus in improving the quality of Akhlak instruction within the pesantren environment.